2016
DOI: 10.1016/j.pt.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

All For One and One For All on the Tick–Host Battlefield

Abstract: The saliva of ixodid ticks contains a mixture of bioactive molecules that target a wide spectrum of host defense mechanisms to allow ticks to feed on the vertebrate host for several days. Tick salivary proteins cluster in multigenic protein families, and individual family members display redundancy and pluripotency in their action to ameliorate or evade host immune responses. It is now clear that members of different protein families can target the same cellular or molecular pathway of the host physiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 52 publications
2
113
0
Order By: Relevance
“…The primary line of host defense also relies on complex hemostatic and immunological responses of the host against ectoparasites. For example, ticks counteract the host response and successfully survive attached to the skin of their host via the secretion of a complex mixture of molecules present in tick saliva (Rodriguez-Valle et al, 2010;Chmelar, 2016;Xu et al, 2016). Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary line of host defense also relies on complex hemostatic and immunological responses of the host against ectoparasites. For example, ticks counteract the host response and successfully survive attached to the skin of their host via the secretion of a complex mixture of molecules present in tick saliva (Rodriguez-Valle et al, 2010;Chmelar, 2016;Xu et al, 2016). Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others.…”
Section: Discussionmentioning
confidence: 99%
“…Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others. These reports concluded that tick proteins secreted into the tick's attachment site inhibit host hemostatic and immunological responses by diverse mechanisms (Francischetti et al, 2009) sequences which leads to important structural modifications that affect their specific functions (Schwarz et al, 2014;Chmelar, 2016). Also, peptide members of the Kunitz protein family have diverse activities in venomous scorpions and spiders eg LmKKT-1a, huwentoxin-1, huwentoxin-2, and magi-1 families that inhibit proteases and ion channels (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirudin isolated from leeches possesses strong anticoagulation ability and has been used in antithrombotic therapy and in combination with tumor chemotherapy and radiotherapy. Ticks are blood-feeding ectoparasitic arthropods that produce various bioactive molecules that display both pluripotency and redundancy, particularly proteins present in the saliva and saliva gland [27]. Other studies have described different native and recombinant proteins with antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…In ticks, CRTs are important components of tick saliva, which plays a pivotal role in tick feeding and pathogen transmission to hosts by acting as anti-haemostatic, anti-inflammatory and immunomodulatory molecules [715]. In this context, CRTs have been suggested to play a modulating role in host haemostasis [9, 16, 17] and have been shown to be highly immunogenic to tick mammalian hosts [1821].…”
Section: Introductionmentioning
confidence: 99%